Efficacy and safety of intracoronary pro-urokinase combined with low-pressure balloon pre-dilatation during percutaneous coronary intervention in patients with anterior ST-segment elevation myocardial infarction - Shicheng Yu; Haoxuan Jia; Shengkai Ding; Mengda Zhang; Fengyun Li; Pan Xu; Yuan Tian; Lingling Ma; Lijie Gong; Jun Feng; Zhaojin Sun; Fudong Qian; et al. (Journal of Cardiothoracic Surgery, 2024)
Abstract Background The efficacy and safety of low-pressure balloon pre-dilatation before intracoronary pro-urokinase (pro-UK) in preventing no-reflow during percutaneous coronary intervention (PCI) remains unknown. This study aimed to evaluate the clinical outcomes of intracoronary pro-UK combined with low-pressure balloon pre-dilatation in patients with anterior ST-segment-elevation myocardial infarction (STEMI). Methods This was a randomized, single-blind, investigator-initiated trial that included 179 patients diagnosed with acute anterior STEMI. All patients were eligible for PCI and were randomized into two groups: intracoronary pro-UK combined with (ICPpD group, n = 90) or without (ICP group, n = 89) low-pressure balloon pre-dilatation. The main efficacy endpoint was complete epicardial and myocardial reperfusion. The safety endpoints were major adverse cardiovascular events (MACEs), which were analyzed at 12 months follow-up. Results Patients in the ICPpD group presented significantly higher TIMI myocardial perfusion grade 3 (TMPG3) compared to those in the ICP group (77.78% versus 68.54%, P = 0.013), and STR ≥ 70% after PCI 30 min (34.44% versus 26.97%, P = 0.047) or after PCI 90 min (40.0% versus 31.46%, P = 0.044). MACEs occurred in 23 patients (25.56%) in the ICPpD group and in 32 patients (35.96%) in the ICP group. There was no difference in hemorrhagic complications during hospitalization between the groups. Conclusion Patients with acute anterior STEMI presented more complete epicardial and myocardial reperfusion with adjunctive low-pressure balloon pre-dilatation before intracoronary pro-UK during PCI. Trial registration 2019xkj213.